REPRESENTASI REMAJA DALAM SERIES ADOLESCENCE (2025) - Nikita Audia Pradita; Muhammad Bayu Widagdo (Interaksi Online, 2026)
Adolescence is a crucial stage of development characterized by complex physical, psychological, and social changes. During this period, adolescents are expected to begin behaving more maturely; however, they often do not possess full autonomy over themselves. This condition makes adolescents vulnerable to unequal power relations and social discrimination, one of which appears through negative stereotypes portraying them as problematic, emotional, rebellious, and difficult to manage. Such perceptions are further reinforced through media representations, including films and television series. One series that explores adolescent issues is Adolescence (2025), a British psychological crime series that portrays adolescent characters through various social and emotional conflicts. Therefore, this study aims to examine how adolescents are represented in the series Adolescence (2025). This study employs a qualitative approach using John Fiske’s semiotic analysis method, which consists of three levels of coding: the level of reality, the level of representation, and the level of ideology. The findings reveal that adolescents are portrayed as unequal through various aspects, including behavioral dominance, camera techniques, camera angles, lighting, narrative, and other cinematic elements. Adolescents are also negatively represented as emotional, difficult to control, withdrawn, and vulnerable to violent behavior. Furthermore, adolescents are depicted as a social group that is controlled and excessively regulated, as reflected in the dominance of adult authority across various aspects of adolescent life. Based on these findings, it can be concluded that Adolescence (2025) tends to strongly emphasize the negative aspects of adolescence. The series has the potential to normalize stereotypes that problematic behavior is an inherent characteristic of adolescents. However, the series also offers criticism of the overly simplistic ways society and adults perceive adolescents.